Finding the optimal balance: father-athlete challenges facing elite Nordic skiers - Bergström, Max; Solli, Guro Strøm; Sandbakk, Øyvind; McGawley, Kerry; Sæther, Stig Arve (Frontiers in Sports and Active Living, 2024)
Background In the last decade, a growing body of research has focused on the many aspects and challenges of combining parenthood with elite sport. Although the number of father-athletes is significantly higher than the number of mother-athletes, few studies to date have focused on male athletes’ experiences in a parenting context. Aim The aims of the present study were to explore how father-athlete challenges manifest among elite Nordic skiers in Norway, and to better understand how male athletes balance their priorities as they initiate, maintain, and/or discontinue their athletic career as a father-athlete. Methods Qualitative data were collected through semi-structured interviews with 10 world-class male Nordic skiers in Norway (3 athletes without a child, 4 current father-athletes and 3 former father-athletes) and the content was analyzed using thematic analysis. Results Four main stages were identified in the father-athlete transition: (a) Expecting incompatibility (b) Taking the step, (c), The first blow, and (d) Finding the optimal balance. Through these stages the informants expected/had experienced challenges such as performance decline, disturbed sleeping patterns, fear of sickness and role conflicts. To manage these challenges, the father-athletes had developed various strategies to balance their dual roles (e.g., adapting training and competition seasons). Among the benefits, the father-athletes mentioned that they had become more structured, time efficient and ruthless with their priorities, enhanced motivation to train and a better work-life balance. Conclusion This study offers valuable insights into father-athlete challenges that can be used to support career longevity and work-life balance among male athletes.